A Curative Perspective on Down Syndrome - Rondal, Jean A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
A curative perspective on Down syndrome is pointing out. Experimental work regarding chromosome correction and corrective action on genes and proteins is yielding positive results. They open the way to advances in dealing with aneuploidies and may end up markedly changing the life of the individuals affected with these conditions at the same time, several molecules are in the research pipeline of cognitive pharmacotherapy. The paper summarizes these advances and set them into perspective for the future of Down syndrome. Research on the effects of the amyloid cascade in the etiology of Alzheimer disease, which is more frequent in aging persons with Down syndrome, is also analyzed. Its potential for improving early diagnosis and paving the way for stabilizing the condition at least in the first stages is also discussed.